2021
DOI: 10.3389/fphys.2021.702248
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term and Lifelong Exercise Training Lowers Inflammatory Mediators in Older Men

Abstract: Increased basal low-grade inflammation is observed with advancing age, which is augmented by physical inactivity. However, data regarding the influence of lifelong exercise training and particularly high-intensity interval training (HIIT) on inflammatory mediators in older men are scarce. Therefore, we examined effects of 6weeks of aerobic preconditioning followed by 6weeks of HIIT on inflammatory mediators [interleukin (IL)-6, homocysteine, and high-sensitivity C-reactive protein (hsCRP)] in previously sedent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 66 publications
2
4
0
Order By: Relevance
“…Interestingly, the associations between physical performance tests and the inflammatory phenomenon found after resuming training in the group of older men can reinforce the previous suggestion that stronger and faster volunteers might generate better conditions to mitigate the development and progression of inflammaging [23,27]. However, the lack of associations between these parameters in older women can suggest that ten months of resuming physical training is not enough to promote the same regulatory effect found in older men, although it was sufficient for the ratios between pro-inflammatory (IL-6, IL-8, TNF-α) and anti-inflammatory (IL-10) cytokines to become similar to the pre-pandemic period.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Interestingly, the associations between physical performance tests and the inflammatory phenomenon found after resuming training in the group of older men can reinforce the previous suggestion that stronger and faster volunteers might generate better conditions to mitigate the development and progression of inflammaging [23,27]. However, the lack of associations between these parameters in older women can suggest that ten months of resuming physical training is not enough to promote the same regulatory effect found in older men, although it was sufficient for the ratios between pro-inflammatory (IL-6, IL-8, TNF-α) and anti-inflammatory (IL-10) cytokines to become similar to the pre-pandemic period.…”
Section: Discussionsupporting
confidence: 80%
“…Although the systemic levels of IL-6, IL-8, IL-12p70, and IL-10 were higher at PRE, and these findings putatively suggested that long-standing physical exercise would drive the systemic state toward a pro-inflammatory direction, the data obtained in the ratios between pro-and anti-inflammatory cytokines, in general, demonstrated an inflammatory status regulated pre-pandemic [40], a significant deregulation during detraining phase [28,51], and a "return" of regulated status with the resumption of exercise training [19]. Interestingly, a study carried out with twenty-two healthy and sedentary older men, with an average age of 62 years, showed that six weeks of high-intensity aerobic training was capable of reducing serum levels of C-reactive protein and IL-6 to values similar to those of older adult athletes who practiced competitive sports (running, swimming and cycling) for more than thirty years [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HIIT is typically around or below 100% VO 2max whilst SIT is all-out, an intensity above VO 2max [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Both HIIT and SIT are reportedly efficacious in improving VO 2max at sea level [ 19 , 21 , 22 , 23 , 24 , 25 , 26 ]. The understanding that exercise intensity is a potent stimuli for improving VO 2max is not a new discovery [ 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this effect, our study suggests that young athletes might activate repair mechanisms more efficiently than master athletes immediately after exercise. This is likely due to the chronic adaptation resulting from years of training in master athletes, which leads to less pronounced acute inflammatory signaling [5,23,47]. Whether the lack of significant change in MCP-1 levels may impair immediate repair responses (i. e. inadequate immune cell recruitment) or such adaptations could reflect a minimizing excessive inflammation while optimizing recovery and repair processes in master athletes should be explored by further studies.…”
Section: Discussionmentioning
confidence: 99%